The consequences of knowledge hiding behavior in organizations: a systematic literature review - Alaydi, Bader; Bali Mahomed, Anuar Shah; Ng, Siew Imm; Cheah, Jun Hwa (Asociacion de Economia Aplicadad, 2021)
This study aims to provide a systematic review regarding the consequences of knowledge hiding in the organization by ascertaining, synthesizing and evaluating theoretical, methodological and empirical dimensions of other works in the field. Design/methodology/approach: applying systematic review methodology to present the current consequences of knowledge hiding behavior in organizations. Findings: all of the studies indicated that knowledge hiding behavior hurts organizational performance and develop unhealthy working environments. Limitations/ implications: this systematic review is designed only to present a conceptual synthesis of existing works. A meta-analysis to an empirical study to obtain a more detailed framework is encouraged. Originality/value: this study contributes to organizational behavior literature by identifying the consequences of knowledge hiding, presenting the different methodological frameworks used to establish the relationships between knowledge hiding and their consequences, and to introduce the gaps for future researches.